Tumor-related denervation pseudohypertrophy of the tongue: A clinical entity in disguise! - Mukherjee, Anindya; Satheesh Babu, Thotten Vettil; Muttath, Geetha; Nayanar, Sangeetha (Indian Journal of Case Reports, 2018)
Isolated hypoglossal nerve palsy in the base of tongue carcinomas is seldom noticed. The clinical signs are subtle in early stageand can often be overlooked. There may be slight tongue deviation to the affected side, and the tongue feels soft and edematouson careful palpation. There may be associated enlargement of the affected side of the tongue known as “pseudo hypertrophy” dueto denervation of its motor supply. Contrast-enhanced magnetic resonance imaging is the gold standard of diagnosis which showsdiffuse fatty changes in the affected half of tongue with the preservation of architecture. Clinicians need to be aware of this clinicalentity to distinguish it from actual tumor invasion.